2021
DOI: 10.1038/s41598-021-81962-6
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a TF–miRNA–gene feed-forward loop network predicts biomarkers and potential drugs for myasthenia gravis

Abstract: Myasthenia gravis (MG) is an autoimmune disease and the most common type of neuromuscular disease. Genes and miRNAs associated with MG have been widely studied; however, the molecular mechanisms of transcription factors (TFs) and the relationship among them remain unclear. A TF–miRNA–gene network (TMGN) of MG was constructed by extracting six regulatory pairs (TF–miRNA, miRNA–gene, TF–gene, miRNA–TF, gene–gene and miRNA–miRNA). Then, 3/4/5-node regulatory motifs were detected in the TMGN. Then, the motifs with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…A total of 31 TFs were identified by a series of comprehensive analyses. Recently, numerous studies ( 38 40 ) have demonstrated that TFs regulate gene expression by interacting with miRNAs. Thus, the associations between the miRNAs and TFs were further investigated using the miRWalk database.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 31 TFs were identified by a series of comprehensive analyses. Recently, numerous studies ( 38 40 ) have demonstrated that TFs regulate gene expression by interacting with miRNAs. Thus, the associations between the miRNAs and TFs were further investigated using the miRWalk database.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complex pathogenesis of MG and the side effects of drugs, no one treatment therapy is best for all MG patients. In the past few years, we have tried to adopt several different methods, such as constructing miRNA-regulated drug-pathway network [41] and TF-miRNA-gene feed-forward loop network [42], to screen candidate treatment drugs for MG. Recently, the combination of emerging nanotechnologies and material sciences has promising applications in multiple fields, such as nanotechnology in food and agriculture [43], nano-antioxidants in environmental-related oxidative damages [44] and nanotechnology on drug delivery in autoimmune diseases [45].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fast network motif detection (FANMOD) software was used to detect network motif types of size-3 in the original network ( Wernicke and Rasche, 2006 ). The method of generating motifs by FANMOD software can be found in our previous study ( Bo et al, 2021 ). Finally, 3-node motif types with Z-score >2.0 and p -value < 0.05 were considered to be significant in the dumping results of multiple types of motifs ( Harari and Liao, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study ( Bo et al, 2021 ), we mentioned two types of pivotal gene regulators: transcription factors (TFs) and miRNAs, both sharing a common regulatory logic in the co-regulation of target genes ( Hobert, 2008 ). Besides, gene regulators (miRNA and TF) and their common target gene can make up a feed-forward loop (FFL), a motif that consists of two regulators and their common target gene ( Mangan and Alon, 2003 ).…”
Section: Introductionmentioning
confidence: 99%